Phytochrome and light influence on germination and vigor of ocimum gratissimum L. (Lamiaceae) seeds under high irradiance conditions - Rocha, S. F R [UNESP]; Scarda, F. M. [UNESP] (My University, 2002)
Ocimum gratissimum seed germination (% germination and vigor) has been found as phytochrome dependent, having a typical High Irradiant Response (HIR). Seven treatments were tested: daylight (DL), red (R), far-red (FR), blue (B), green (G), dark (DK), and reversible (RVB). No statistical difference among the DL, R, FR, B, and G were found. DK and RVB were statistically equal and presented the lowest results. The germination also occurred in the DK treatment but in non-useful rates, and it was nonreversible in the RVB treatment. It allows these seeds to be classified as positively photoblastic. The minimum energy need to initiate the germination was evaluated by a fluency-response curve. It plotted four different exposition times to R light (1 second, 60 seconds, 1 hour, and 13 hours) against percent germination. Useful germination occurred only after 1 hour, confirming the high energy needed to incite the process. The germination rate increased with the raise of the photoequilibrium (j). The high positive correlation index found confirms the phytochrome influence in this process. Facing all the results presented here, it is suggested to sow these seeds under direct and highly intense sunlight. It is preferable to avoid places exposed to variations in the shading, because inhibition induced by dense shade effects (low R/FR ration and consequently low j established) were demonstrated irreversible, and it can lead to undesirable loss of the germination power.
Keywords: Ecophysiology; Light quality; Medicinal plants.; Ocimum gratissimum; Photoblasty; Photoequilibrium; Seed germination